What Can We Tell Our Patients About Rheumatoid Arthritis Risk? (Canadian Rheumatology Today, 2025)
You are seeing a 45-year-old female with a chief complaint of joint pain in the hands and feet. The symptoms have been apparent for 6 months. There was no preceding illness. She reports morning stiffness of the affected joints. The patient denies any joint swelling. Her medical history is notable for a strong family history of Rheumatoid Arthritis, and she currently smokes one pack of cigarettes daily. On physical examination, the joints appear normal, with full range of motion and no obvious tenderness to palpation. There is no evidence of synovitis or rashes. Laboratory investigations show elevated anti-citrullinated protein antibody level of 135, and her rheumatoid factor level is 45. C-reactive protein is within normal limits. Radiographs of the hands and feet are normal.Questions:1. What is her likelihood of developing rheumatoid arthritis within the next 3 years?2. Are there any other tests you need to order?3. Can rheumatoid arthritis be prevented in this individual? What advice can you provide her?